Tapping into the potential of okra (Abelmoschus spp.) in Africa: integrating value-added traits into breeding - Ayenan, Mathieu A. T.; Vihou, Fabrice; Ambali, Mwasilwa; Opoku, Jacinta Adoma; Ibiotye, Dorcas Olubunmi; Schafleitner, Roland (Frontiers in Plant Science, 2025)
Okra is a nutritious vegetable of global significance. This crop serves various purposes and presents numerous untapped opportunities. However, several challenges hinder Africa from fully harnessing okra’s economic and nutritional benefits, including pest and disease pressures, salinity and cold stress, weak seed systems, insufficient market knowledge, and a lack of value addition. A wealth of okra genetic resources is conserved in gene banks worldwide; however, only a handful have been characterized for agronomic and value-added traits, limiting their use in breeding programs. Although traditional breeding has focused on enhancing yield, disease resistance, and pod quality traits, which remain important, the growing demand for new okra-based products such as pectin, oil, snacks, and coffee substitutes offers new opportunities for farmers, processors, and breeders. Meeting these demands will require incorporating value-added traits into breeding programs, as identified in this review. Understanding the diversity of okra germplasm for value-added traits, their genetic architecture, and developing efficient screening methods is crucial for creating improved varieties that meet the needs of farmers, processors, and consumers. Enhancing the value-added traits of okra will increase production to meet the rising demand. We identified key traits of interest for improvement across different okra uses. Improving okra for biotic and abiotic challenges, as well as integrating horticultural and value-added traits, requires an in-depth understanding of the okra market to define and prioritize market segments along with target product profiles that fulfill their requirements, increased investment in okra breeding, collaboration between public and private seed and processing firms, resource sharing, and strengthening seed systems. Building capacity in okra breeding and seed technologies is critical to catalyzing okra improvement in Africa.